Organisational and leadership skills towards healthy workplaces: an interview study with registered nurses in Sweden - Kristina Rosengren; Malin Friberg (BMC, 2024)
Abstract Background According to shortage of registered nurses, organisational and leadership aspects grounded in person-centrered approach, are highlighted to ensure high quality of care. Therefore, it is interesting to develop knowledge regarding registered nurses working environment. Aim The aim of the study was to investigate registered nurses' reason to end their employment at a university hospital setting (internal medicine, emergency department). Method Qualitative content analysis with an inductive methodological approach was used to analyse registered nurses' experiences regarding their former employment. Inclusion criteria; all nurses (n = 55) who ended employment during one year (first of July 2020-30th of June 2021) were invited, and 38 semi-structured interviews were conducted. Results Three categories were identified: Limited organisational support, Lack of visible leadership, and Limited healthy working environment, followed by six subcategories: Longing for organisational support, Being a tile in a box, Need for professional relationship, Limitation of supportive leadership, Imbalance of work versus personal life, and Ethical stress. Conclusion To improve registered nurses working environment and commitment to work, balance between time at work and personal life is significant. Therefore, organisational support and leadership skills grounded in a person-centred approach are crucial to develop a healthy working environment. A person-centred leadership could improve collaboration and shared decision-making in partnership with those involved, managers, nurses, and team members.